Design and fabrication of the second generation IIUM buggy car - Abdullah, Kassim Abdulrahman (s.n, 2012)
This report provides the detailed information involved in the design and fabrication of the Second generation IIUM buggy car. All details regarding the method of design, design philosophy, concept and model construction, result evaluation, and fabrication processes are included. Selecting right materials with appropriate dimensions can reduce the overall weight of the car while accurate design collaboration within the suspension system can ensure a better maneuver characteristic. A number of design options have been generated. The best option chosen was based on a lightweight buggy car with high strength performance, good handling characteristic as well as excellent driver’s ergonomic aspect.